Angioaccess for hemodialysis in kidney transplantation: Hemodynamic implications for the left heart (International Journal of Medical and Surgical Sciences, 2021)
Cardiovascular complications represent the main cause of morbidity and mortality in patients with chronic renal disease, so the objective of this article is to demonstrate the influence of the patency of the arteriovenous fistula on echocardiographic variables measured in the left heart. For this, a multivariate study, longitudinal, prospective and controlled study of independent groups after an intervention that included 39 patients who had their angioaccess closed (study group) and 42 who were not exposed to surgery (control group). Both groups exhibited functional kidney transplantation. The main results emerge when comparing the prevalence between the study group and the control group, the average age; 45.6 and 44.1 years, the male sex, 24 (60%) and 23 (53.5%) and the white skin color; 33 (82.5%) and 32 (74.4%). The most frequent etiology of the original nephropathy was hypertensive vascular nephropathy; 12 (30%) vs 14 (32.6%). Among the clinical manifestations, remission of palpitations and dyspnea on exertion were evidenced in the study  group. With regard to blood pressure, for the systolic it ranged from 123 ±13.4 to 120.5 ±9.2 vs. 125.6 ±8.4 to 128 ±8.3 mmHg (p= 0.000), while the diastolic varied from; 76.8 ±7.5 to 76.3 ±6.2 vs. 78.6 ±4.9 to 82.4 ±3.9 mmHg (p= 0.000). The hematocrit had equivalent values; 0.43 ±0.06 and 0.45 ±0.06 vs 0.42 ±0.05 and 0.42 ±0.06 l/l (p= 0.035) and the serum creatinine showed decrease in the operated patients from; 106.8 ±26.2 to 99.8 ±23.9 μMol/l vs 114 ±27.8 to 120.3 ±31 μMol/l (p= 0.002). The echocardiographic variables measured comparatively according to the location of the angioaccesses at the left elbow level; diameter of the left ventricle: 3.12 ±4.08 vs 1.48 ±3.46 mms (p=0.001), ejection fraction of the left ventricle: 2.99 ±5.47 vs -1.98 ±6.23 % (p=0.018) and the telediasolic volume: -23 ±33.41 vs 10.86 ±36.87 ml (p=0.006). The contralateral elbow revealed; for the left ventricular ejection fraction: 3.32 ±3.42 vs -2.18 ±4.78 % (p=0.037) and for cardiac output: -1.29 ±0.88 vs -0.26 ±0.86 l/min (0.020). The conclusions show that the our study has shown that closing the angioaccess to patients with functioning renal transplants with respect to those not operated, contributes to the regression of morphological and hemodynamic alterations observed by transthoracic echocardiography in the left heart at the different locations of the vascular accesses.
Keywords: Renal transplantation; arteriovenous fistula